A history of fascism in France : from the First World War to the National Front - Millington, Chris (Bloomsbury Academic, 2020)
"A History of Fascism in France explores the origins, development, and action of fascism and extreme right and fascist organisations in France since the First World War. Synthesizing decades of scholarship, it is the first book in any language to trace the full story of French fascism from the First World War to the modern National Front, via the interwar years, the Vichy regime and the collapse of the French Empire. Chris Millington unpicks why this extremist political phenomenon has, at times, found such fervent and widespread support among the French people. The book chronologically surveys fascism in France whilst contextualizing this within the broader European and colonial frameworks that are so significant to the subject. Concluding with a useful historiographical chapter that brings together all the previously explored aspects of fascism in France, A History of Fascism in France is a crucial volume for all students of European fascism and France in the 20th century."--